The Gewanci Application Media based on Smart Apps Creator on the Material of Imitating Animal Movements - Rahmi Amalia Utami; Deasylina da Ary (Journal of Education Reseach and Evaluation, 2024)
In learning Cultural Arts in the realm of Dance, grade 1 teachers at SD Kanisius Beringin Semarang have not effectively utilized available learning resources; therefore, new media development is needed. The researcher aims to develop, determine the feasibility results, and test the effectiveness of the Smart Apps Creator-based Gewanci application media on the material of Imitating Animal Movements.This kind of study is referred to as development research using the ADDIE model. The research subjects consisted of media experts and material experts. The test was conducted on twenty three students who were in grade 1 of SD. This research use quantitative data to examine development. Data is collected via many methods such as observation, interviews, questionnaires, and testing. Data collection is conducted using a Likert Scale questionnaire. Data analysis encompasses quantitative, qualitative, and inferential statistical methodologies. The result of this research is to produce a learning media in the form of Gewanci Application which distinguishes itself from other applications, namely there are 15 videos of movement imitating rabbit animals, accompanied by attractive images and audio. This application is specifically designed to be in line with the teaching material. The findings of the media and material validation scores indicate that there are a total number of material validation scores with a percentage validation value of 93.7%. This suggests that these scores are very practical. Furthermore, media validation was considered very realistic, with a validation value percentage of 91%. Based on the t-test results, the use of the Gewanci application media has a significant impact. The N-gain test revealed a moderate improvement in learning outcomes from the pretest to the posttest. The findings suggest that the Gewanci app, developed using Smart Apps Creator, adequately meets the needs of dance education.